2011
DOI: 10.1097/pas.0b013e31822067d1
|View full text |Cite
|
Sign up to set email alerts
|

Nonhepatosplenic γδ T-cell Lymphomas Represent a Spectrum of Aggressive Cytotoxic T-cell Lymphomas With a Mainly Extranodal Presentation

Abstract: γδ T-cells represent a minor T-cell subset mainly distributed in mucosal surfaces. Two distinct lymphomas derived from these cells have been recognized: hepatosplenic γδ T-cell lymphoma (HSTL) and primary cutaneous γδ T-cell lymphoma (PCGD-TCL). However, whether other anatomic sites may also be involved and whether they represent a spectrum of the same disease is not well studied. The lack of TCRβ expression has been used to infer a γδ origin when other methods are not available. We studied 35 T-cell tumors su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 35 publications
(35 reference statements)
5
101
0
Order By: Relevance
“…Estimation of the γδ-TCR antibody is controversial. A study using the same antibody (TCR gamma+delta antibody clone 5A6.E9) can successfully recognize γδ-T-cells with membranous staining in formalin-fixed paraffin-embedded tissue, 22 but there was another one reporting that the antibody was not so robust. 23 Although membranous positive-staining of γδ-TCR is acceptable as positive, we need further study for γδ-TCR.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of the γδ-TCR antibody is controversial. A study using the same antibody (TCR gamma+delta antibody clone 5A6.E9) can successfully recognize γδ-T-cells with membranous staining in formalin-fixed paraffin-embedded tissue, 22 but there was another one reporting that the antibody was not so robust. 23 Although membranous positive-staining of γδ-TCR is acceptable as positive, we need further study for γδ-TCR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of type II EATL showed that about 80% expressed TCRgd [10], suggesting that it might be one example of the nonhepatosplenic gd T-cell lymphomas increasingly recognized [21]. Owing to the retrospective nature of this study, TCR immunophenotype was not available in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…in five cases. TCRc or TCRd was detected in all cases, with simultaneous expression of bF1 in one case [74,75]. All cases express cytotoxic granules that include granzyme B, perforin, and TIA-1.…”
Section: Primary Cutaneous CD T-cell Lymphomamentioning
confidence: 92%
“…Its histological findings are variable and include upper dermal infiltration with marked epidermotropism with ulceration of the epidermis, diffuse dermal infiltration, or involvement of the subcutis with a subcutaneous panniculitis-like pattern [74]. Most patients experience an aggressive clinical course with extranodal and nodal dissemination [74,75]. The identification of primary cutaneous cdTCL was difficult until the TCRc and TCRd antibodies for paraffinsection immunohistochemistry became available commercially.…”
Section: Primary Cutaneous CD T-cell Lymphomamentioning
confidence: 99%